Interpretation of 'Omics dynamics in a single subject using local estimates of dispersion between two transcriptomes - Li, Qike; Zaim, Samir Rachid; Aberasturi, Dillon; Berghout, Joanne; Li, Haiquan; Vitali, Francesca; Kenost, Colleen; Zhang, Helen Hao; Lussier, Yves A (AMIA ... Annual Symposium proceedings, 2019)
Calculating Differentially Expressed Genes (DEGs) from RNA-sequencing requires replicates to estimate gene-wise variability, a requirement that is at times financially or physiologically infeasible in clinics. By imposing restrictive transcriptome-wide assumptions limiting inferential opportunities of conventional methods (edgeR, NOISeq-sim, DESeq, DEGseq), comparing two conditions without replicates (TCWR) has been proposed, but not evaluated. Under TCWR conditions (e.g., unaffected tissue vs. tumor), differences of transformed expression of the proposed individualized DEG (iDEG) method follow a distribution calculated across a local partition of related transcripts at baseline expression; thereafter the probability of each DEG is estimated by empirical Bayes with local false discovery rate control using a two-group mixture model. In extensive simulation studies of TCWR methods, iDEG and NOISeq are more accurate at 5%<DEGs<20% (precision>90%, recall>75%, false_positive_rate<1%) and 30%<DEGs<40% (precision=recall~90%), respectively. The proposed iDEG method borrows localized distribution information from the same individual, a strategy that improves accuracy to compare transcriptomes in absence of replicates at low DEGsconditions. http://www.lussiergroup.org/publications/iDEG.